Association of Calcium and Phosphate Levels with Incident Chronic Kidney Disease in Patients with Hypoparathyroidism: A Retrospective Case-Control Study - Elvira O. Gosmanova; Olulade Ayodele; Kristina Chen; Erin E. Cook; Fan Mu; Joshua A. Young; Lars Rejnmark (International Journal of Endocrinology)
Objective. Reasons for the increased incidence of chronic kidney disease (CKD) in patients with chronic hypoparathyroidism are poorly understood. This study evaluated associations between levels of albumin-corrected serum calcium, serum phosphate, and calcium-phosphate product and the odds of CKD development in patients with chronic hypoparathyroidism. Design. A retrospective nested case-control study of adult patients with chronic hypoparathyroidism who had ≥1 prescription for calcitriol who developed CKD and matched controls who did not develop CKD were selected from the IBM® Explorys electronic medical record database. Patients. The study included a cohort of 300 patients for the albumin-corrected serum calcium analysis and 80 patients for the serum phosphate and calcium-phosphate product analyses. Measurements. We examined associations between albumin-corrected serum calcium, serum phosphate and calcium-phosphate product levels, and the risk of devloping CKD (defined as ≥2 outpatient estimated glomerular filtration values <60 mL/min/1.73 m2 occuring ≥3 months apart or ≥1 diagnostic code for CKD stages 3–5). Results. Individuals who had ≥67% of albumin-corrected serum calcium measurements outside, above, or below the study-defined range (2.00–2.25 mmol/L [8.0–9.0 mg/dL]) had 3.5-, 2.9-, and 2.7-fold higher odds of developing CKD (adjusted odds ratios [95% CI]: 3.46 [1.82–6.56], 2.85 [1.30–6.28], and 2.68 [1.16–6.15]), respectively, compared with patients who had <33% of albumin-corrected calcium measurements in those ranges. There was no association between developing CKD and having any serum phosphate measurements or any calcium-phosphate product measurements above normal population ranges. Conclusion. In adult patients with chronic hypoparathyroidism, a higher proportion of albumin-corrected calcium measurements outside of the 2.00–2.25 mmol/L (8.0–9.0 mg/dL) range was associated with higher odds of developing CKD.